A study of learning environments in the Kulliyyah (faculty) of nursing, International Islamic University Malaysia - Nurumal, Mohd. Said; Rogayah, Jaafar; Hafizah, Arzuman (Universiti Sains Malaysia, 2009)
Background: In a nursing programme, the main objective is to produce nursing graduates who can provide comprehensive care and treatment to the community. A good approach to the systematic design of a learning environment can lead to positive outcomes for graduates. The learning environment is more than student-teacher interaction, teaching and learning activities. Good physical structures and facilities provided by the university are important, too. Furthermore, the university must also be concerned about meeting studentsï¿½ psychosocial and emotional needs. The aim of this study is to measure the learning environment by administering the Dundee Ready Educational Environment Measure (DREEM) questionnaire to students across the four years of the Bachelor of Nursing programme at the Faculty of Nursing, IIUM, and to identify areas for change that may contribute to a more meaningful student learning experience. Methods: The DREEM questionnaire was administered to 105 Bachelor of Nursing students at IIUM. Results: The total mean score on the 50-item DREEM inventory was 120.12 out of a maximum of 200. Student perceptions of learning and their teachers, their academic self, social self and their perception of the atmosphere were all positive. Eight items with low mean scores (less than two) on the DREEM questionnaire were identified as requiring remediation. Conclusion: The implications include the need to create and maintain a supportive environment, in addition to designing and implementing interventions to remedy unsatisfactory elements of the learning environment if effective and successful teaching and learning are to be realised. Thus, specific remedial steps to improve the student learning environment of the Faculty of Nursing, IIUM are described.